Analisis e interpretacion a los estados financieros del comisariato de la Universidad Nacional de Loja, periodos 2005-2006-2007. - Quezada Quizhpe, Naila Jhoana (2010)
The present work of investigation titled “Analysis and Interpretation to the States Financial of Comisariato of the National University of Loja periods 2005-2006-2007” were carried out based on the general norms of graduation it foresaw to opt the grade of graduates in Accounting and Audit. The analysis applied to the Financial States of Comisariato of National University of Loja, it was carried out with the purpose of knowing their economic situation financial and the level of their administrators’ management, for we carry out it a vertical analysis ending up knowing the financial situation of every period, we apply indexes related with the activity that acts in the Comisariato to be able to determine their liquidity, solvency, profitability and level of indebtedness; being able to fulfill the objectives outlined in this project what you/they reflect the obtained results. The carried out investigation consists of: They SUMMARIZE that is a recapitulation of the thesis work; INTRODUCTION where is exposed the importance of the realization of a financial analysis and the contribution from this to the entity in that it applies it to him; REVISION OF LITERATURE, in which consists the bibliographical summary of the analysis, their different methods, indicators and report; MATERIALS AND METHODS that it stands out the materials, methods and techniques that were used during the investigation; DISCUSSION AND RESULTS, he/she shows up the application from the analysis to the Financial States of Comisariato; CONCLUSIONS AND RECOMMENDATIONS, where the most outstanding aspects in the analysis process are described in order to that the directive take the due corrections; BIBLIOGRAPHY, in which you/they consist the sources of information used in the development of the present work; ANNEXES, in which copies of the Financial States of Comisariato of the analyzed years are included.